The dynamics of delight : architecture and aesthetics - Smith, Peter F. (Peter Frederick), 1930- (Routledge, 2003)
This book rounds off decades of exploration into the various ways that buildings and urban sequences make an impact on the mind.
Keywords: Architecture -- Aesthetics.; Architecture -- Psychological aspects.; Architecture -- Esthétique.; Architecture -- Aspect psychologique.; ARCHITECTURE -- Urban & Land Use Planning.; Architecture -- Aesthetics; Architecture -- Psychological aspects